INFLUENCE OF GUIDANCE AND COUNSELLING SERVICES ON REDUCTION OF DRUG ABUSE AMONG UNDERGRADUATE STUDENTS IN PUBLIC UNIVERSITY CAMPUSES IN NAIROBI COUNTY, KENYA - Pere, Joyce G. (International Journal of Psychology, 2018)
Purpose: The study aimed at establishing the extent to which guidance and counselling services influence reduction of drug abuse among undergraduate students in public university campuses in Nairobi County, Kenya. Methods: The study used Triangulation mixed methods design that adopted convergent parallel mixed method model. Cross-sectional survey research design was used for quantitative data while phenomenological design for qualitative data. Stratified random sampling and purposive sampling was used to select the sample. The sample consisted of one thousand, five hundred and twenty four (1524) participants who included 1500 students, 20 peer counsellors, two university counsellors and two deans of students. Questionnaires, interview and Focus Group Discussions (FGD) guides were used to collect data. Statistical Package for Social Science (SPSS) version 21 was used to analyse quantitative data while NVIVO was used to analyse qualitative data. Descriptive statistics were used in analysis of quantitative data while thematic and content analysis techniques were used to analyse qualitative data. Results: The researcher concludes that parents have contributed to continuous abuse of drugs among students rendering the preventative strategies ineffective. Unique contribution to theory, practice and policy: The study recommends that the university administration should ensure that drug abuse policies are pinned on all notice boards particularly on students' notice boards so that they can read them every time they are checking on what is new on the notice boards. Keywords: Guidance, counselling services, reduction, drug abuse, undergraduate students, public university campuses, Nairobi County, Kenya